2019
DOI: 10.3390/agronomy9100609
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Inorganic Nitrogen Fertilizer with Green Manure (GM) Increased Yield Stability by Improving C Input and Nitrogen Recovery Efficiency in Rice Based Cropping System

Abstract: A long-term field experiment was carried out (since 2008) for evaluating the effects of different substitution rates of inorganic nitrogen (N) fertilizer by green manure (GM) on yield stability and N balance under double rice cropping system. Treatments included, (1) N0 (no N fertilizer and no green manure); (2) N100 (recommended rate of N fertilizer and no green manure); (3) N100-M (recommended rate of N fertilizer and green manure); (4) N80-M (80% of recommended N fertilizer and green manure); (5) N60-M (60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 73 publications
3
10
1
1
Order By: Relevance
“…There is a wide range of legume crops that have a superior capacity to fix atmospheric N, and therefore can be used for green manuring under aerobic rice systems ( Qaswar et al, 2019 ). Annual N accumulation by legume crops ranges between 20 kg ha –1 and 300 kg ha –1 ( Thind et al, 2012 ; Ali et al, 2015 ).…”
Section: Toward Better N Managementmentioning
confidence: 99%
“…There is a wide range of legume crops that have a superior capacity to fix atmospheric N, and therefore can be used for green manuring under aerobic rice systems ( Qaswar et al, 2019 ). Annual N accumulation by legume crops ranges between 20 kg ha –1 and 300 kg ha –1 ( Thind et al, 2012 ; Ali et al, 2015 ).…”
Section: Toward Better N Managementmentioning
confidence: 99%
“…Stubbles also have the ability to incorporate nitrogen into soil, which is one of the main elements for synthesizing proteins. Rice yield is achieved with the contribution of nitrogen from stubble and reduce the cost of chemical fertilizers [26]. The combination of stubble with chemical fertilizers such as urea significantly increases wheat yields and minerals such as nitrogen and organic carbon [27].…”
Section: Crop Yieldmentioning
confidence: 99%
“…To achieve better yield and quality, rice growers have applied large amounts of nitrogen (N) fertilizer in different seasons of rice production. Excessive application of N fertilizer not only increased the probability of lodging and reduces the yield and quality of rice, but also leads to potential environmental risks [3,4]. At present, few studies have reported on N fertilizer incorporation technology for rice planting several times a year in South China.…”
Section: Introductionmentioning
confidence: 99%